EFEKTIVITAS MEDIA PERMAINAN SIMULASI DAN MEDIA GAMBAR PERISTIWA TERHADAP PRESTASI BELAJAR MATERI TEKS DISKUSI - Hidayatullah, M. Jihad; Haryadi, Haryadi (Diksi, 2018)
Abstract(Title: The Effectiveness of Simulation Game Media and Event Pictures Media in Improving Learning Achievement in Discussion Text). This study aims to determine the issues concerning  whether there is any significant difference among the students achievement in discussion text of bahasa Indonesia tested using simulation game media, event picture media, and other conventional media and whether there are any significant differences among the effectiveness of simulation game media, event picture media, and other conventional media in improving the achievement in discussion text of bahasa Indonesia for junior high school students in West Lombok. The data were collected through a multiple choice test abd analyzed by using ANOVA and Scheffe test using SPSS. The results of these study are: First, there are significant differences among the students achievement in discussion text of bahasa Indonesia tested using simulation game media, event picture media, and other conventional media, with F = 23,717 and p < 0,05. Second, there are any significant differences among the effectiveness of simulation game media, event picture media, and other conventional media in improving the achievement in discussion text of bahasa Indonesia for junior high school students with conclusion; (1)  the use of simulation game media is more effective than the use conventional media, with with a mean difference 15,166 and sig < 0,05; (2) the use of event picture media is more effective than the use conventional media, with a mean difference 22,386 and sig < 0,05; (3) the use of simulation game media is less effective than the use of event picture media, with a mean difference -7.220 and sig > 0,05.Keywords: simulation game media, event pictures media, discussion text.